The Relationship between Nutritional Status and Mother Parenting on Child Development at 24-59 Months of Age in Palembang City - amrina rosyada; Putria Friti Ichsani (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2026)
Indonesia has 13-18% of child development problems such as motor delays, language, behavior, autism, and hyperactivity. In South Sumatra, the prevalence of stunting is 24.8%, wasting 7.6%, and obesity 4.9%. Parenting and nutritional status are recognized factors influencing child development because if it is not in accordance with the needs of the child it is possible to inhibit the growth and development of toddlers. The purpose of this study was to determine the relationship between nutritional status and mother parenting patterns on child development aged 24-59 months in Palembang city. The study employed quantitative research methods with a cross-sectional design and the population was families with toddlers aged 24-59 months who lived in Palembang City in four sub-districts namely Sukarami District, Kemuning District, Ilir Barat I District, Alang-Alang Lebar District. The sampling technique used was purposive sampling based on the predetermined criteria with a sample size of 128 children under five. The results showed there was no relationship between nutritional status and mother parenting patterns on child development aged 24-59 months in Palembang City (p-value = 0.332) and there was a relationship between mother parenting with the development of children aged 24-59 months in Palembang City (p-value = 0.000) with a PR value: 2,590. The conclusion of this study states that there is no relationship between nutritional status and mother parenting patterns on child development aged 24-59 months in Palembang City. Keywords: Child development, Maternal parenting, Nutritional status